FDG PET‐CT imaging in head and neck paragangliomas: A centre experience. (30th May 2021) - Boughdad, Sarah; O'Connor, Ann; Cook, Gary J.; Pike, Lucy; Connor, Steve; Obholzer, Rupert; Warbey, Victoria
Abstract: Head and neck paragangliomas (HNPGLs) are rare tumours with ~ 30% genetic mutations, mainly in succinate dehydrogenase (SDHx) genes. The utility of FDG PET‐CT in HNPGLs is questioned by recent developments in novel radiotracers. We therefore performed a retrospective study in a single tertiary referral centre to address the utility of FDG PET/CT in HNPGLs. Methods: Clinical data on genetic testing and follow‐up were collected for patients who had FDG PET‐CT scans from 2004 to 2016. Receiver operator characteristic (ROC) analysis was used to compare standardized uptake values (SUVs), metabolic tumour volume (MTV) and total lesion glycolysis (TLG) between lesions in patients who had a clinically related event: event (+) and those who did not: event (−). Similarly, we compared PET parameters between SDHx+ patients and a control group with low probability of mutation. Results: Of 153 HNPGL patients, 73 (29 SDHx+) with 93 FDG‐positive lesions were identified: 53.8% of lesions were assessed in a pre‐therapeutic setting. In comparison with a reference extracted from clinicoradiological database, FDG PET‐CT showed good performance to detect HNPGLs (96.6% accuracy). In this study population, 16 disease progression, 1 recurrence and 1 death were recorded and event (+) patients had lesions with higher SUVmax ( p  = .03 and p  = .02, respectively) . Conversely, there were no differences in PET parameters between lesions in SDHx+ patients and controls with low probability of SDHx+ mutations. Conclusions: FDG PET‐CT has clinical utility in HNPGLs, mostly before local treatment. There were no significant differences in PET parameters between SDHx patients and a sporadic HNPGL population. However, regardless of SDHx mutation status, a high SUVmax was associated with more clinical events and prompts to a closer follow‐up.